2019
DOI: 10.1088/1361-648x/ab5907
|View full text |Cite
|
Sign up to set email alerts
|

Coupled plasmon–phonon modes in monolayer MoS2

Abstract: We present a theoretical study of the plasmon-phonon coupling in a suspended monolayer MoS 2 and a MoS 2 substrate system using a diagrammatic self-consistent field theory. The four coupled plasmon-phonon modes and the four plasmon-surface phonon modes are observed due to the spin-orbit and electron-optic phonon interactions. The two of coupled plasmonphonon and plasmon-surface phonon modes are optic-like and the other two are acoustic-like. The plasmon are strongly coupled with the optic-phonon in MoS 2 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, plasmons can hybridize with phonons and produce a vibrational (phonon) mode of several GHz frequency that is comparable to the frequencies of SWs in ferromagnetic media. [13][14][15][16] Ref. [14], specifically, dealt with a monolayer system (MoS 2 ) and showed that four modes are produced as a result of phonon-plasmon coupling in that system, two of which are optical in nature and two are acoustic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, plasmons can hybridize with phonons and produce a vibrational (phonon) mode of several GHz frequency that is comparable to the frequencies of SWs in ferromagnetic media. [13][14][15][16] Ref. [14], specifically, dealt with a monolayer system (MoS 2 ) and showed that four modes are produced as a result of phonon-plasmon coupling in that system, two of which are optical in nature and two are acoustic.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Ref. [14], specifically, dealt with a monolayer system (MoS 2 ) and showed that four modes are produced as a result of phonon-plasmon coupling in that system, two of which are optical in nature and two are acoustic. The latter have frequencies in the range of zero to optical phonon frequencies and hence span the range of GHz frequencies that are the frequencies of spin waves in our systems.…”
Section: Introductionmentioning
confidence: 99%
“…These particular plasmonic properties have a non-trivial influence on superconductivity that is qualitatively different from phonon mediated mechanisms. Additionally, the low-energetic gapless plasmon allows for efficient hybridization between plasmons and longitudinal optical phonons [55]. Thus, in contrast to conventional 3D superconductors, in which plasmons have large gaps, a fully momentum-dependent and dynamical theory is required to accurately describe 2D superconductors in the presence of electron-phonon and electron-electron interactions [34,35,[37][38][39][56][57][58].…”
Section: Introductionmentioning
confidence: 99%